Photocurrent improvement of an ultra-thin silicon solar cell using cascaded cylindrical shape plasmonic nanoparticles. (22nd February 2021) - Heidarzadeh, Hamid; Bahador, Hamid
Abstract: The main aim of this research work is to significantly improve the photocurrent of an ultra-thin silicon solar cell. Here, cylindrical shape cascaded plasmonic nanoparticles are used to design an ultra-thin silicon solar cell. The main idea is to manipulate the absorption spectra of a thin absorber by applying four cascaded cylindrical shape nanoparticles from different materials with different radii and heights. At first, a cell with one nanoparticle at the surface and another one with a nanoparticle at the bottom side are simulated, and their photocurrents are determined. Then, a cell with four cascaded Ag, Al, Ag-Al, and Al-Ag nanoparticles is simulated. The maximum photocurrent density and efficiency of 23.46 mA cm −2 and 13.95%, respectively, are obtained for a cell in which Ag and Al's nanoparticles are used alternatively from top to bottom. The photocurrent density is 8.2 mA cm −2 for a cell without any nanoparticles. The simulated results show that cascaded nanoparticles significantly enhance the photocurrent. Finally, the generation rate is presented at different wavelengths.